Nejlepší světové čtení - Meade, Glenn, 1957-; Baldacci, David, 1960-; Connelly, Michael, 1956-; Delinsky, Barbara, 1945-; Janiš, Viktor, 1974-; Strenk, Michal; Popel, Jiří, 1955-; Vlasáková, Jana (Nejlepší světové čtení, 2001)
Edice zkrácených verzí nejlepších románů současných autorů.